Lacan’s Construction and Deconstruction of the Double-Mirror Device - Vanheule, Stijn (Frontiers in Psychology, 2011)
In the nineteen fifties Jacques Lacan developed a set-up with a concave mirror and a plane mirror, based on which he described the nature of human identification. He also formulated ideas on how psychoanalysis, qua clinical practice, responds to identification. In this paper Lacan’s schema of the two mirrors is described in detail and the theoretical line of reasoning he aimed to articulate with aid of this spatial model is discussed. It is argued that Lacan developed his double-mirror device to clarify the relationship between the drive, the ego, the ideal ego, the ego ideal, the other and the Other. This model helped Lacan describe the dynamics of identification and explain how psychoanalytic treatment works. He argued that by working with free association, psychoanalysis aims to articulate unconscious desire, and bypass the tendency of the ego for misrecognition. The reasons why Lacan stressed the limits of his double-mirror model and no longer considered it useful from the early nineteen sixties onward are examined. It is argued that his concept of the gaze, which he qualifies as a so-called ‘object a,’ prompted Lacan move away from his double-mirror set-up. In those years Lacan gradually began to study the tension between drive and signifier. The schema of the two mirrors, by contrast, focused on the tension between image and signifier, and missed the point Lacan aimed to address in this new era of his work.